Academic stress and irregular menstruation influence the dysmenorrhea, school absenteeism and healthcare seeking among adolescent girls in junior high school in Shanghai: a cross-sectional study - Liu, Tiantian; Qi, Deyun; Zhang, Li; Hou, Jun; Zhao, Jing; Zhou, Yuan; Sun, Bingbing; Wang, Fei; Tan, Hui; Wang, Ruiping (Frontiers in Reproductive Health, 2025)
BackgroundDysmenorrhea is a cramping pain during menstrual period and the leading cause for recurrent short-term school absenteeism among adolescent girls. However, evidence on the factors associated with the occurrence of dysmenorrhea, school absenteeism and health care seeking behavior among adolescent girls is still limited, especially in China. This study aim to understand the prevalence of dysmenorrhea and to explore factors associated with the school absenteeism and healthcare seeking habit among adolescent girls with dysmenorrhea.MethodsThis cross-sectional,questionnaire-based study included 1,243 participants recruited from five junior high schools using cluster sampling method. Data were collected through a structured questionnaire interviews and SPSS 22.0 was used for data analysis.ResultsThe prevalence of dysmenorrhea was 67.2%. Logistic regression analysis indicated that adolescent girls in grade 8 (OR = 1.98, 95% CI: 1.32–2.97) and grade 9 (OR = 2.32, 95% CI: 1.54–3.48), whose mothers had a college and above education (OR = 1.85; 95% CI: 1.12–3.07), those with controllable learning burden (OR = 1.69, 95% CI: 1.10–2.60) and uncontrollable learning burden (OR = 2.04, 95% CI: 1.10–3.80) had higher prevalence of dysmenorrhea. Logistic regression indicated that adolescent girls with normal weight (OR = 0.60, 95% CI: 0.43–0.83) had lower proportion of school absenteeism, and adolescent girls with uncontrollable learning burden (OR = 2.73, 95% CI: 1.29–5.75) and with irregular menstruation (OR = 1.74, 95% CI: 1.26–2.39) had higher proportion of school absenteeism. Moreover, underweight adolescent girls, adolescent girls whose mother had senior high education and those with irregular menstruation had a higher proportion of healthcare seeking experience.ConclusionsDysmenorrhea was common among adolescent girls in junior high schools in Shanghai, and academic stress as well as irregular menstruation was positively associated with dysmenorrhea and school absenteeism. More attention and intervention measures focusing on menstrual health problems should be implemented directly among adolescent girls in junior high school, especially among those with low body weight, irregular menstruation, and academic stress. Most importantly, this study provides scientific evidence on adolescent dysmenorrhea issues, offering targeted recommendations for policymakers to advance the refinement and implementation of public health policies.